Investigations of the livelihood strategies of young men and women in forested landscapes of eastern Cameroon - MacNeil, C.; Brown, H.C.P.; Sonwa, D.J. (Commonwealth Forestry Association, 2017)
In rural African settings, people maintain diversified livelihood strategies to reduce risks and garner income. Although youth are currently the dominant demographic and an important group within forest communities of Central Africa, little is known about their dependence on the forest for their livelihoods. Given that young people are underrepresented in research studies, this study aimed to understand whether young people (aged 19–30) gain a large proportion of their livelihood from forest resources (including agroforestry). Focus groups and surveys were conducted in six villages in Eastern Cameroon to identify subsistence and income-driven activities of young people. In the context of many changes, young people continue to derive a large proportion of their livelihood from forest resources, especially agroforestry. Changes in livelihood activities were noted in the gender division of work and access to resources. Environmental pressure is likely to impact the livelihoods of these forest communities into the future.